2022
DOI: 10.21037/atm-22-2768
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Sanfeng Tongqiao Diwan in patients with allergic rhinitis: a single-arm clinical trial in China

Abstract: Background: Traditional Chinese medicine (TCM) has a long history and its own characteristics in the treatment of allergic rhinitis. In this study, the efficacy and safety of patients with allergic rhinitis treated with Sanfeng Tongqiao Diwan were observed to support the clinical medication of patients with allergic rhinitis.Methods: A total of 61 patients with allergic rhinitis aged 12-70 years from the First Affiliated Hospital of Guangzhou Medical University were included in this study. All the patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…No drug-related side effect was observed during the treatment period in the 2 groups. A previous study reported that the major AEs could include mild rash, with an incidence rate of 3.3%, which resolved without any intervention ( 4 ). The increase in blood eosinophils in the placebo group after 2 weeks was likely related to uncontrolled inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No drug-related side effect was observed during the treatment period in the 2 groups. A previous study reported that the major AEs could include mild rash, with an incidence rate of 3.3%, which resolved without any intervention ( 4 ). The increase in blood eosinophils in the placebo group after 2 weeks was likely related to uncontrolled inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Sanfeng Tongqiao Diwan contains Scutellaria baicalensis (Huang qin), Schizonepeta tenuifolia (Jing jie), Asarum sieboldii (Xi xin), and Notopterygium incisum (Qiang huo). It has the actions of clearing heat and dispelling wind, dispelling cold, and opening orifices and can significantly improve the symptoms of acute sinusitis and allergic rhinitis, with no drug-related adverse reactions being observed in related studies ( 3 , 4 ). In this study, 60 patients with UACS were selected as the research participants to evaluate the clinical efficacy and safety of Sanfeng Tongqiao Diwan in the treatment of UACS and to provide new approaches for the treatment of UACS with prepared TCM.…”
Section: Introductionmentioning
confidence: 99%